Historyczne znaczenie zasady in poenalibus causis benignius interpretandum est - Zalewski, Bartosz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Poszukując historycznych korzeni zasady humanitaryzmu, która w pewien sposób determinuje instytucjonalne ukształtowanie norm prawa karnego i zasad ich wykładni, zwykło się wskazywać na okres oświecenia. Trzeba jednak zauważyć, że dyrektywy wykładni nakazujące stosować interpretację możliwie najkorzystniejszą dla sprawców czynu przestępnego znało już prawo rzymskie. Jedną z nich była niewątpliwie zasada in poenalibus causis benignius interpretandum est. Przedmiotem rozważań w niniejszym artykule są dzieje tytułowej paremii, począwszy od jej sformułowania przez rzymskiego jurystę Paulusa, aż po prawo kanoniczne XX w.

Searching the historical roots of the humanitarianism principle, which in some way determines the institutional shaping of the legal norms of criminal law and the rules of their interpretation, it is usual to point to the period of Enlightenment. However it should be noted, that the directive requiring the most favorable interpretation for the perpetrators was already known to Roman law. One of them was undoubtedly the principle in poenalibus causis benignius interpretandum est. The subject of this paper is the history of the title legal maxim, from its formulation by the Roman jurist Paulus to the canon law of the twentieth century.
Keywords: rzymskie prawo karne; historia prawa; humanitaryzm; wykładnia prawa; Roman criminal law; legal history; humanitarianism; interpretation of law